Assessment of Metadata Quality of the Swedish National Bibliography through Mapping User Awareness. Issue 1 (2nd January 2018) - Häusner, Eva-Maria; Sommerland, Ylva
ABSTRACT: This article is examining if the metadata quality of the Swedish National Bibliography could be measured through mapping the level of user awareness regarding the characteristics of the data. A qualitative meta-synthesis was carried out and results from two previous studies conducted at the National Library of Sweden were interpreted and conceptualized through an integrated analyze. The results of the meta-synthesis showed a need for an action plan for increasing user awareness to efficiently reach target groups of national bibliographic data at its fullest potential, i.e. user awareness on the usability and the quality of the metadata.